Exploring Students' Perceptions of Narrative Role-Play Videos in Speaking Assessment - Shafira, Setya Esti; Rokhayati, Titi; Chasanah, Zulia (Journal of English Language and Education, 2025)
Speaking assessment using video role-playing games provides an engaging and realistic alternative for assessing speaking ability. Despite its potential, research exploring students' perceptions of this assessment method is limited.  This study aims to describe students' perceptions of narrative role-play videos as a speaking assessment. This study used a qualitative descriptive approach, with thematic analysis to analyze the data. Meanwhile, data were collected from 30 eleventh grade students at MAN Purworejo through an open-ended questionnaire. The findings showed that the majority of students had a positive perception of the method, highlighting benefits such as increased vocabulary, fluency, and confidence, although some experienced technical difficulties. Overall, the use of narrative role-play videos became a more interactive and relevant speaking assessment method, while improving students' communicative competence.